Sanctioned Violence in the New Testament - Carter, Warren (Interpretation, 2017)
After describing key interpretive categories of sanctioned and structural violence, the article identifies some forms of sanctioned structural violence evident in Matthew’s Gospel. It concludes with a brief consideration of contemporary strategies for identifying and resisting scriptural inscribing and sanctioning of violence.